1998
DOI: 10.1038/sj.bmt.1701302
|View full text |Cite
|
Sign up to set email alerts
|

Foscarnet vs ganciclovir for cytomegalovirus (CMV) antigenemia after allogeneic hemopoietic stem cell transplantation (HSCT): a randomised study

Abstract: Summary:This trial was designed to compare foscarnet with ganciclovir as pre-emptive therapy for CMV infection in patients undergoing allogeneic hemopoietic stem cell transplant (HSCT). Thirty-nine patients were randomized to receive foscarnet 90 mg/kg every 12 h (n = 20) or ganciclovir 5 mg/kg every 12 h (n = 19) for 15 days at the time of development of CMVAg-emia. Primary-end points of the study were (1) outcome of CMVAg-emia; (2) progression to CMV disease; and (3) side-effects of treatment. The secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 22 publications
(20 reference statements)
5
43
1
Order By: Relevance
“…First results suggest that preemptive foscarnet treatment mediates protection from CMV disease in SCT recipients. 19,21 We report the results of a prospective randomized multicenter trial in which foscarnet and ganciclovir were compared in the preemptive therapy of CMV infection after allogeneic SCT. In this study, antiviral treatment was initiated upon detection of CMV by antigenemia assay or by PCR in peripheral blood leukocytes, and was given for no longer than 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…First results suggest that preemptive foscarnet treatment mediates protection from CMV disease in SCT recipients. 19,21 We report the results of a prospective randomized multicenter trial in which foscarnet and ganciclovir were compared in the preemptive therapy of CMV infection after allogeneic SCT. In this study, antiviral treatment was initiated upon detection of CMV by antigenemia assay or by PCR in peripheral blood leukocytes, and was given for no longer than 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Using antigenemia-based assays, 60-85% of patients have been reported to clear viremia after 2 weeks of therapy. 10,12,16,19 When PCRbased surveillance strategies are employed, clearance rates of 37-50% have been reported after 2 weeks. 9,11 In our series, 36/58 patients (62%) had negative shell vial cultures recorded on day 14 of LDSC GCV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous series using abbreviated inductionmaintenance schedules of GCV have reported a much higher incidence of neutropenia with about a third of patients developing an ANCo1000/ml and up to 20% of patients exhibited a decline in their ANC to o500/ml. [9][10][11]13,14,16,17 A substantial proportion of patients in these series also required growth-factor support that adds substantially to the overall cost of therapy. More importantly, Salzberger et al 5 have shown that neutropenia in patients receiving GCV is an independent risk factor for poor long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7) Three studies have so far identified risk factors for ganciclovir-induced neutropenia. Tomonari et al reported that reduced renal function was a risk factor for ganciclovir-induced neutropenia following cord blood transplantation.…”
mentioning
confidence: 99%